AN INVESTIGATION INTO LINGUISTIC FEATURES OF ANTITHESIS USED IN “MY LIFE” BY BILL CLINTON - NGUYỄN MINH HIỀN (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis was conducted to examine and describe the syntactic, semantic and pragmatic features of antithesis used in “My Life” by Bill Clinton. In order to obtain these aims, a quantitative method, a qualitative method and a contrastive analysis method are taken into account. The study focused on discovering the common distinctive linguistic characteristics of antithesis in “My Life” to figure out the effects of antithesis in catching readers’ attention. The data of the study were collected from 600 examples in “My Life” by Bill Clinton which were used to make the contrastive analysis to support the objectives of the study. Finding revealed the predominance of antithesis used in “My Life”. Antithesis in terms of syntax was considered. Especially, noun phrases expressed contrasting ideas occurred with high frequency to strike the important information, to attract readers’ attention and to give powerful utterances. In terms of semantic fields, antithesis was used to show the politics and economics way during his presidency. Furthermore, antithesis was exploited effectively in showing many pragmatic features such as complimenting, showing humanity, making emotional effects, etc. to reflect the writer’s idea and to emphasize the effectiveness of antithesis in persuading and attracting the readers to the context of the story. Through an investigation into linguistic features of antithesis used by Bill Clinton in “ My Life”, the researcher hopes to bring out some certain benefits to the readers, the language teachers and learners. Basing on the findings and results, the study put forwards some implications in the English language teaching and learning in the hope that they could be beneficial for not only English teachers but also for learners of English.